One and two-photons excitation of aminonaphthalimide–bodipy dyads: biological application - Vida-Pol, Yolanda (My University, 2014)
Boron dipyrromethene (BODIPY) dyes are commonly commercialized chromophores that have attracted immense interest as versatile tools in biological chemistry. However, the generally very small Stokes shifts of BODIPY dyes may cause re-absorption or effects from excitation-light scattering, which is a potential drawback for their application, especially in bioimaging. One strategy to avoid this problem is the integration of BODIPY dyes as acceptors in bi- or multichromophoric arrays, some of them qualifying as energy transfer cassettes where donor and acceptor units are electronically non-conjugated. In this communication we present a series of aminonaphthalimide–BODIPY energy transfer cassettes that shown very fast and efficient BODIPY fluorescence sensitization. This was observed upon one- and two-photon excitation, which extends the application range of the investigated bichromophoric dyads in terms of accessible excitation wavelengths. In comparison with the direct excitation of the BODIPY chromophore, the two-photon absorption cross-section  of the dyads is significantly incremented by the presence of the aminonaphthalimide.The applicability of the new probes in the one- and two-photon excitation mode was demonstrated, both in solution and supported on silica nanoparticles, in a proof-of-principle approach in the fluorescence imaging of HeLa cells.
Keywords: Fotoquímica; Two photon excitation